2020
DOI: 10.1038/s41467-020-17155-y
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning for genomics using Janggu

Abstract: In recent years, numerous applications have demonstrated the potential of deep learning for an improved understanding of biological processes. However, most deep learning tools developed so far are designed to address a specific question on a fixed dataset and/or by a fixed model architecture. Here we present Janggu, a python library facilitates deep learning for genomics applications, aiming to ease data acquisition and model evaluation. Among its key features are special dataset objects, which form a unified… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 18 publications
0
55
0
Order By: Relevance
“…To further improve the results, it is necessary to consider the cell type when predicting promoters and enhancers. It has been shown that promoter prediction can also be improved using extra information as input, for example chromatin data 39 or possibly applying nonparametric methods as described and tested on promoter regions of a model dicot plant Arabidopsis thaliana 40 . However, the approach described in this paper has the advantage that it is very general.…”
Section: Discussionmentioning
confidence: 99%
“…To further improve the results, it is necessary to consider the cell type when predicting promoters and enhancers. It has been shown that promoter prediction can also be improved using extra information as input, for example chromatin data 39 or possibly applying nonparametric methods as described and tested on promoter regions of a model dicot plant Arabidopsis thaliana 40 . However, the approach described in this paper has the advantage that it is very general.…”
Section: Discussionmentioning
confidence: 99%
“…With the growing popularity of DL methods for analyzing sequencing data, several software frameworks and packages specifically designed for bioinformatics data have been introduced recently. Libraries, such as Nucleus [48] or Janggu [49] , can be used alongside Keras, TF, or PyTorch. They offer dedicated objects for processing biological sequence data, which makes it easy to read, write, analyze, and visualize data in common genomics file formats, such as BAM, FASTA, bigWig, VCF, or BED.…”
Section: Deep Learning Frameworkmentioning
confidence: 99%
“…Tailored ML frameworks and platforms that account for the idiosyncrasies of the underlying data have been published for applications in genomics 38,39 , proteomics 40,41 , biomedicine 42 , and chemistry 43 . Their creation recognizes the infeasibility to define, implement, and train appropriate ML models by relying solely on generic ML frameworks such as scikit-learn 44 or PyTorch 45 .…”
Section: Introductionmentioning
confidence: 99%